A binder-free sulfur/carbon composite electrode prepared by a sulfur sublimation method for Li–S batteries. Issue 58 (31st May 2016) - Cui, Yi; Wu, Min; Scott, Charity; Xie, Jiani; Fu, Yongzhu
Abstract : A binder-free sulfur/carbon composite electrode was prepared by a sulfur sublimation method. Sulfur nanoparticles fill large pores in a carbon paper substrate and the composite electrode shows a long cycle life of over 200 cycles in Li–S batteries. Abstract : A binder-free sulfur/carbon composite electrode was prepared by a sulfur sublimation method. Sulfur nanoparticles fill large pores in a carbon paper substrate and primarily have a monoclinic crystal structure. The composite electrode shows a long cycle life of over 200 cycles with good rate performance in Li–S batteries.